"I remember the skills we learned and put them into practice": An Evaluation of a Peer Support Training Program for Veterans - Karen Besterman-Dahan; Jacqueline Siven; Kiersten Downs; Tatiana Orozco (The University of Alabama, 2022)
Community-based organizations (CBOs) are critical sources of support for veterans. CBOs offer innovative and informed initiatives and are often nexuses that allow veterans and their allies to gather. Out of a commitment to veteran reintegration, Growing Veterans (GV), a veteran-founded CBO located in western Washington, created and implemented an evidence-based peer support training program (PST) for veterans and their allies. Building upon years of collaboration, GV partnered with the Veterans Health Administration (VHA) to conduct a formative evaluation of GV's PST program, funded through the Bob Woodruff Foundation. The evaluation revealed that participants described the PST in largely positive ways and reported using learned skills with both veterans and nonveterans across their personal and professional lives. Specifically, participants reported learning tools through the PST that increased their patience, mindfulness, awareness, empathy, and confidence, resulting in improved interpersonal relationships and communications across multiple domains. The success of this community-engaged collaboration was due in part to the inclusion of veterans, allies, GV employees, and VHA evaluators throughout the evaluation, from grant applications to the final analysis. Using ethnographic methods of participant observation, in-depth interviews, focus groups, and surveys, VHA evaluators were able to gain a deep understanding of participants' experiences of the PST as well as the program's perceived usefulness.